(Re)visão do Paraíso: uma leitura ecológica do Éden religioso na obra de Sérgio Buarque de Holanda para os dias atuais - Noli, Giordano Bruno (2023)
The work aims to understand how the Myth of Adam and Eve influenced our current way of relating with nature. To that end, Sérgio Buarque de Holanda's work, Vision of Paradise, in which the author develops the idea of edenism, a representation that permeated the sixteenth-century imaginary about American lands, is used as a theoretical path for reflections on the cultural-ecological aspects of our vision of human beings and nature that led us to the present moment